(untitled) (International Journal of Food and Nutritional Sciences, 2022)
AIM- The aim of the present investigation is to study Preliminary Phytochemical & In-Vitro Evaluation of Anti-diabetic Activity of Roots of Plumbago zeylanica. MATERIAL & METHODS- The roots of the selected medicinal plant was procured from the local market ayurvedic shop. The root part of selected plant was dried under shade and processed for the successive solvent extraction method. All the extracts were dried under vacuum and subjected to determination of percentage yield. All the extracts were subjected to preliminary phytochemical screening for the presence of various active Phytoconstituents. Anti-diabetic potential of different extracts were determined by α-amylase and Glucose Diffusion Assay. The dilution of different extracts were prepared in concentration of 10-100µg/ml. RESULTS- The crude drug was extracted by different solvents and solvents were selected according to polarity index i.e. solvents with lower polarity to higher polarity. The dried powders of root were extracted by using Petroleum ether, DCM, Ethyl acetate, Methanol and finally water. On the completion of preliminary phytochemical screening, petroleum ether extract showed presence of steroids and fatty acids. The DCM and ethyl acetate extracts showed presence of alkaloids, flavonoids, and terpenoids. The methanolic and water extracts showed the presence of some flavonoids, glycoside compounds. The anti-diabetic activity of DCM and ethyl acetate extracts showed maximum activity in comparison to other extracts. CONCLUSION- The phytochemical screening of root part showed the presence of various alkaloids and flavonoids.